Galactomannan Antigenemia in Pediatric Oncology Patients With Invasive Aspergillosis - Hayden, Randall (Pediatr Infect Dis J, 2008)
BACKGROUND: Diagnosing invasive aspergillosis is difficult but might be improved by detection of circulating galactomannan. Although galactomannan antigenemia has been well studied in the detection of invasive aspergillosis in adult patients, little is known about the expression of circulating galactomannan in immunocompromised children with invasive aspergillosis. METHODS: We studied the expression of galactomannan antigen by enzyme immunoassay (EIA) in 990 serum samples from 56 pediatric oncology patients (ages 3 months to 18 years) of whom 17 had proven or probable invasive aspergillosis defined by the European Organization for Research and Treatment of Cancer-Mycoses Study Group criteria. Any sample with a galactomannan EIA Galactomannan index value of ≥0.5 was considered positive. RESULTS: At least 1 serum sample was positive for 11 of 17 pediatric oncology patients (65.7% sensitivity, 95% confidence interval: 38.3–85.7) with invasive aspergillosis. Galactomannan EIA was positive in 99 of 304 samples from patients with proven or probable invasive aspergillosis, and 7 of 686 (1.0%) samples from 39 control subjects resulted in a positive galactomannan EIA result. At least 1 sample tested positive in 5 of the 39 controls (12.8%, 95% confidence interval: 4.3–27.4). No significant association between accuracy and patient age was observed. Among the 7 evaluable galactomannan-positive patients with IA, the galactomannan EIA produced a positive result before clinical or radiographic evidence of infection in 6 cases, with a lead-time to diagnosis ranging from 1 day to 34 days (median: 10 days). In the remaining case, a positive galactomannan was observed on the same day as diagnosis by non-EIA methods. CONCLUSIONS: The presence of circulating galactomannan is predictive of invasive aspergillosis in most pediatric oncology patients. Galactomannan antigenemia may precede clinical, microbiologic, or radiographic evidence of invasive aspergillosis.